2022
DOI: 10.3390/su142416396
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Structure of Vegetation Rhizosphere Bacterial Community in Various Habitats of Liaohekou Coastal Wetlands

Abstract: Coastal wetlands are a type of unique ecosystem, in which rhizosphere microorganisms of vegetation play a significant role in the overall ecology. Rhizosphere soil samples from the vegetation of Liaohekou Coastal Wetlands, Northeast China (40°54′44″ N, 121°47′51″ E), were collected in seven habitats (Suaeda and Phragmites community in different coverage, aquaculture ponds and farmland biotopes) to evaluate the diversity and structure of bacterial community using high throughput sequencing. Soil physicochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…FAPROTAX can effectively predict the variations of bacterial ecological functional profiles [47]. The dominant functions were chemoheterotrophy and aerobic chemoheterotrophy involved in C cycling, which is consistent with the research on the main potential functions of other aquatic plants [48]. Heterotrophic bacteria are often used as decomposers and are responsible for in situ pollution repair and degradation of organic matter in ecosystems [49].…”
Section: Functional Prediction Of Bacterial Communities In Different ...supporting
confidence: 79%
“…FAPROTAX can effectively predict the variations of bacterial ecological functional profiles [47]. The dominant functions were chemoheterotrophy and aerobic chemoheterotrophy involved in C cycling, which is consistent with the research on the main potential functions of other aquatic plants [48]. Heterotrophic bacteria are often used as decomposers and are responsible for in situ pollution repair and degradation of organic matter in ecosystems [49].…”
Section: Functional Prediction Of Bacterial Communities In Different ...supporting
confidence: 79%
“…and archaea participate in the chemical cycle of wetland soil ( Mellado and Vera, 2021 ). Liu et al (2022) reported that the S and N cycles were significantly affected by wetland plant composition and coverage with the participation of bacteria. The results of the present study also indicated that the soil S, N, and C cycles were associated with plant diversity, likely through altering the microbial community.…”
Section: Discussionmentioning
confidence: 99%
“…The Liaohe Estuary National Nature Reserve is situated in the Dawei District of Panjin City, Liaoning Province, and the Liaohe Estuary Ecological and Economic Zone. It is not only one of China's largest coastal estuarine wetlands but also one of the most comprehensive coastal wetland ecosystems worldwide [4]. This area not only harbors abundant biological resources but also serves as a breeding ground, wintering ground, and migratory bird stopover for various waterfowl species [5].…”
Section: Introductionmentioning
confidence: 99%